Perbedaan Kemampuan Komunikasi Matematis dan Kemampuan Pemecahan Masalah Matematis Siswa antara Pembelajaran Kooperatif Tipe Student Team Achievment Division dan Pembelajaran Kooperatif Think Pair Share di SMP Nurul Hadina Patumbak - Batas Kaliropan Padang; Mara Samin Lubis; Rusi Ulfa Hasanah (Educational Journal, 2026)
This study aims to determine the differences in mathematical communication ability and mathematical problem-solving ability of students taught using cooperative learning models of the Student Team Achievement Division (STAD) type and Think Pair Share (TPS) type at SMP Nurul Hadina Patumbak. The background of this research is based on the low levels of students’ mathematical communication and problem-solving abilities, caused by the dominance of conventional teaching methods that have not provided students with sufficient opportunities to participate actively in the learning process. This study employed a quantitative approach using a Quasi-Experimental Design with a Non-Equivalent Control Group Design. The study population consisted of all eighth-grade students of SMP YPI Nurul Hadina Patumbak in the 2025/2026 academic year, comprising two classes. Samples were selected using purposive sampling, namely class VIII A (22 students) as Experimental Group I receiving the STAD learning model, and class VIII B (24 students) as Experimental Group II receiving the TPS learning model. The research instrument consisted of essay tests in the form of pretests and posttests to measure mathematical communication ability and mathematical problem-solving ability. Data were analyzed using the Independent Samples t-test and MANOVA with SPSS version 26.0, preceded by normality (ShapiroWilk) and homogeneity (Levene’s Test) prerequisite tests. The results showed that the mean posttest score for mathematical communication ability in the STAD class was 82.27 compared to 78.75 in the TPS class, while the mean posttest score for mathematical problem-solving ability in the STAD class was 84.09 compared to 80.21 in the TPS class. The independent t-test revealed significant differences in mathematical communication ability (t = 2.847; sig. = 0.007) and mathematical problem-solving ability (t = 3.124; sig. = 0.003) between the two classes. The MANOVA results also confirmed a significant simultaneous difference on both dependent variables (F = 7.084; sig. = 0.002). The N-Gain score of the STAD class (0.60) was higher than that of the TPS class (0.52), although both fell within the moderate category. Therefore, it can be concluded that the STAD cooperative learning model is more effective than the TPS model in improving the mathematical communication and problemsolving abilities of eighth-grade students at SMP Nurul Hadina Patumbak.